Seclusion and Restraint of Students With Disabilities: A 1-Year Legal Review. (September 2019) - Prince, Angela M.T.; Gothberg, June
News of teenager's death in California shocked the special education community in early December 2018. Despite the Individuals With Disabilities Education Act's provision for positive behavior supports for students with disabilities, these inidividuals continue to be secluded and restrained at disproportionately higher rates than their nondisabled peers. Using the Special Ed Connection® database, the authors identified 11 court cases from 2018 and analyzed their contents based on individualized education program (IEP) behavior components, type of restraints used, and prevalence of seclusion. Within these cases, all 12 included students were boys, four IEPs included behavior components, nine students were physically or mechanically restrained, and two were secluded. A review of the four cases that included the use of positive behavior supports is included.